Nutrient Enrichment Improves Growth and Food Quality of Two Strains of the Economic Seaweed Pyropia haitanensis - Xu, Ningning; Xu, Kai; Wang, Wenlei; Xu, Yan; Ji, Dehua; Chen, Changsheng; Xie, Chaotian (Frontiers in Marine Science, 2020)
Chinese coastal waters are subject to eutrophication because of rapid economic development and population growth. To study the effects of nutrient enrichment on the growth and quality of Pyropia haitanensis, the thalli of a red-brown (Z-61) strain and a green (Z-26) strain of P. haitanensis were cultured semi-continuously for 15 days in four media with different nitrogen and phosphorus concentrations. High-nutrient conditions had no significant effect on the growth rate of Z-26 and Z-61. Higher concentrations of nutrients increased the chlorophyll a content of Z-61 and Z-26 by 116.7% and 34.2%, respectively. High concentrations of nutrients also significantly increased the average phycoerythrin and phycocyanin contents by 57.4% and 56.0%, respectively (strain Z-61); and by 37.7% and 44.7%, respectively (strain Z-26). As the nitrogen and phosphorus concentrations increased, the mean contents of total protein, essential amino acids, and flavor amino acids increased by 130.0%, 102.5%, and 341%, respectively, for strain Z-61, and by 25.1%, 23.9%, and 497%, respectively, for strain Z-26. Under high-nutrient conditions, the mean total amino acids content was 40.7% higher in Z-26 than in Z-61; the total flavor amino acids content was 117% higher in Z-61 than in Z-26; but there was no significant difference in the total essential amino acids content between the two strains. Interestingly, under low-nutrient conditions, Z-26 had a higher nutritional value than Z-61, but Z-61 tasted better than Z-26. Based on the results of these laboratory experiments, nutrient enrichment might enhance the market value of P. haitanensis by significantly improving its food quality.